Global longitudinal strain by CMR improves prognostic stratification in acute myocarditis presenting with normal LVEF. (11th May 2022) - Porcari, A; Merlo, M; Baggio, C; Gagno, G; Andreis, A; Rosmini, S; Raafs, A; Bromage, D; Cannata', A; Di Bella, G; Nucifora, G; Perazzolo Marra, M; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Prognostic stratification of acute myocarditis (AM) presenting with normal left ventricular ejection fraction (LVEF) relies mostly on late gadolinium enhancement (LGE) characterization (1). Purpose: Left ventricular peak global longitudinal strain (LV-GLS) measured by feature tracking analysis might improve prognostication of AM presenting with normal LVEF (2, 3). Methods: Data of patients undergoing cardiac magnetic resonance (CMR) for clinically suspected AM in seven European Centres (2013-2020) were retrospectively analysed. Patients with AM confirmed by CMR and LVEF ≥50% were included. LGE was visually characterized: localized vs. diffuse, subepicardial vs midwall. LV-GLS was measured by dedicated software. The primary outcome was the first occurrence of an adverse cardiovascular event (ACE) including cardiac death, life-threatening arrhythmias, development of heart failure or of LVEF <50%. Results: Of 389 screened patients, 256 (66%) fulfilled inclusion criteria: median age 36 years, 71% males, median LVEF 60%, median LV-GLS -17.3%. CMR was performed at 4 [2-12] days from hospitalization. At 27 months, 24 (9%) patients experienced ≥1 ACE (71% developed LVEF <50%). Compared to the others, patients experiencing ACEs had lower median LV-GLS values (-13.9% vs -17.5%, p=0.001). At Kaplan-Meier analysis, impaired LV-GLS (both considered as >-20% or quartiles), diffuse and midwall LGE were associated with ACEs (Figure 1). Patients with LV-GLS ≤-20% did not experience ACEs. LV-GLS remained associated with ACEs after adjustment for diffuse and midwall LGE. Conclusions: In AM presenting with LVEF ≥50%, LV-GLS provides independent prognostic value over LGE characterization, improving risk stratification and representing a rationale for further studies of therapy in this cohort (Figure 2).